2020
DOI: 10.1186/s13018-020-01926-w
|View full text |Cite
|
Sign up to set email alerts
|

Does new instrument for Oxford unicompartmental knee arthroplasty improve short-term clinical outcome and component alignment? A meta-analysis

Abstract: Background The Microplasty (MP) instrumentation designed for the Phase III Oxford mobile-bearing unicompartmental knee arthroplasty (UKA) system is considered a better option to achieve more accurate component positioning and alignment. In the present study, we focused on short-term clinical and radiological outcomes to determine whether the MP instrumentation can reduce the short-term revision rate and occurrence of outliers of metallic components. Methods The literature in PubMed, Embase, the Cochrane Libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The microplasty instrumentation, which was introduced after the OUKRs in this study were implanted and is now routinely used, was designed to make the operation simpler and more reproducible. Several studies have shown that microplasty improves component positioning [34][35][36][37] and decreases the rate of bearing dislocation [38]. It includes instrumentation to accurately determine the height of the tibial cut, which facilitates selecting a Size 4 bearing in young active patients.…”
Section: Discussionmentioning
confidence: 99%
“…The microplasty instrumentation, which was introduced after the OUKRs in this study were implanted and is now routinely used, was designed to make the operation simpler and more reproducible. Several studies have shown that microplasty improves component positioning [34][35][36][37] and decreases the rate of bearing dislocation [38]. It includes instrumentation to accurately determine the height of the tibial cut, which facilitates selecting a Size 4 bearing in young active patients.…”
Section: Discussionmentioning
confidence: 99%
“…The new Oxford Microplasty instruments were introduced along with the cemented Oxford Partial and uncemented Oxford Partial to improve the reproducibility of implant positioning and to minimize tibial bone resection. Two studies comparing Oxford Microplasty to conventional instrumentation showed a reduced risk of malalignment of the femoral component and more accurate tibial bone resection, with less bone loss [21,22]; another study reported reduced revision rates with the new instrumentation [20]. This new instrument set, mostly used for the newest designs, may have influenced the results in favor of the Oxford partial prostheses.…”
Section: Did the Indications For Revision Change Between The Older An...mentioning
confidence: 99%
“…Currently, most MB-UKA procedures are performed by using Microplasty instruments [12]. Tibial osteotomy is performed rst, followed by femoral drilling.…”
Section: Introductionmentioning
confidence: 99%